Assessing the Seroprevalence Against Avian Pneumovirus and Ornithobacterium rhinotracheale in Broilers in Uruguay - Suzuki, K.; Petruccelli, M.; Rodriguez, G.; Trenchi, G.; Giossa, G.; Trenchi, H. (International Journal of Poultry Science, 2010)
The objective of this study was to estimate the true prevalence of individual chickens serologically test-positive against avian pneumovirus and Ornithobacterium rhinotracheale in Uruguay. Seventeen different broiler farms existed in three different provinces in Uruguay were recruited and the 1861 broilers were investigated. Individual-chicken sera were analyzed using a commercial enzyme-linked immunosorbent assay. The overall true seroprevalence was 1.9% [95% Bayesian Credible Interval (BCI): <1-7.4%] and less than 0.1% (95% BCI: 0-<0.1%) against avian pneumovirus and Ornithobacterium rhinotracheale, respectively. The result seroprevalence was relatively lower than that reported by other authors in a neighbouring country Argentina where the infection of these diseases was recently observed. This difference was discussed.